Menemani dari Dalam Pengalaman Bersama Umat Baha’i di Pekanbaru, Riau: Accompanying From Within Experiences with Baha’i Communities in Pekanbaru, Riau - HM, Moh. Said; Syafiah; Imam Hanafi; Moh Masduki (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The Bahá’í community in Indonesia—particularly in Riau—is a religious minority frequently facing social, symbolic, and structural exclusion. This article examines the experience of accompanying the Bahá’í community in Pekanbaru during several of its religious observances, including Ridván, Naw-Rúz, and the Birth of Bahá’u’lláh. Employing a sociological approach and drawing on symbolic interactionism, recognition theory, and James C. Scott’s concept of everyday resistance, this study argues that “accompanying” is not merely a gesture of spiritual solidarity but a meaningful social practice that constitutes symbolic resistance to dominant religious narratives. The findings reveal that through empathetic and non-confrontational daily interactions, interfaith actors subtly challenge the boundaries of religious exclusivism and help create a more equitable spiritual space for marginalized groups. As such, accompanying becomes a form of infrapolitics—an understated yet powerful resistance to structural domination. This article contributes to the discourse on pluralism and interfaith studies in Indonesia by highlighting the importance of social presence as a strategy of cultural liberation and affirmation of dignity for marginalized faith communities.